Does disclosure of food inspections affect business compliance? The case of Berlin, Germany. Issue 1 (3rd January 2017) - Bavorova, Miroslava; Fietz, Anica Veronika; Hirschauer, Norbert
Abstract : Purpose: A whole series of food scandals indicates that misdirected incentives continue to be a source of food risks. Lacking market transparency and the opportunistic use of seemingly profitable opportunities to break the rules cause negative externalities and failure of markets. The purpose of this paper is to investigate the influence of mandatory transparency schemes on food businesses' behavioural drivers and thus on compliance. Design/methodology/approach: The authors use an adopted analytical framework developed by Hirschauer et al. (2012) as the theoretical background. The authors provide an empirical analysis of the effects of a disclosure system on businesses' behavioural drivers in three urban parts of the German capital Berlin. The authors conducted a pen-and-paper survey among food businesses to collect data and used a generalized ordered logit regression model to analyse them. Findings: The results show that the higher the businesses assess the possible negative effects of a negative smiley on sales, the higher the probability of compliance. Considering the immaterial behavioural drivers (protective factors) the authors find the statistical significant influence of a feeling of embarrassment in case of disclosure and the feeling of a fair evaluation on compliance. Thus, the study supports the expectation that disclosure policies affect behavioural drivers and have the potential to steer food businesses' compliance. Practical implications: The study supports the expectation that hygiene controls' disclosure positively affects food businesses' compliance. These findings should be taken into consideration in the ongoing discussion about disclosure. Nowadays, there is no mandatory transparency in Germany due to a strong opposition from businesses and their lobbying groups. Originality/value: The authors conducted a pen-and-paper survey among food businesses in three urban districts of the German capital Berlin, namely, Pankow, Lichtenberg and Marzahn-Hellersdorf in 2014. The food authorities in these districts were the only ones in Germany that had introduced and run a mandatory disclosure system (smiley-system) for food businesses. The results of the inspections were published on the authorities' homepages in the internet, and were displayed in businesses. Thus the data mirror the unique experiences of the only German food businesses that participated in a mandatory transparency scheme.